Expanding genotypic and phenotypic spectrums of LTBP3 variants in dental anomalies and short stature syndrome - Kantaputra P. (2023)
Mutations in LTBP3 are associated with Dental Anomalies and Short Stature syndrome (DASS; MIM 601216), which is characterized by hypoplastic type amelogenesis imperfecta, hypodontia, underdeveloped maxilla, short stature, brachyolmia, aneurysm and dissection of the thoracic aorta. Here we report a novel (p.Arg545ProfsTer22) and a recurrent (c.3107-2A > G) LTBP3 variants, in a Turkish family affected with DASS. The proband, who carried compound heterozygous variant c.3107-2A > G, p.Arg545ProfsTer22, was most severely affected with DASS. The proband's father, who carried the heterozygous variant c.3107-2A > G had short stature and prognathic mandible. The mother and brother of the proband carried the heterozygous variant p.Arg545ProfsTer22, but only the mother showed any DASS characteristics. The c.3107-2A > G and the p.Arg545ProfsTer22 variants are expected to result in abnormal LTPB3 protein, failure of TGFβ-LAP-LTBP3 complex formation, and subsequent disruption of TGFβ secretion and activation. This is the first report of heterozygous carriers of LTBP3 variants showing phenotypes. The new findings of DASS found in this family include taurodontism, single-rooted molars, abnormal dentin, calcified dental pulp blood vessels, prognathic mandible, failure of mandibular tooth eruption, interatrial septal aneurysm, secundum atrial septal defect, tricuspid valve prolapse, and a recurrent glenohumeral joint dislocation.